STRATEGI PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BAITUL MAL WATTAMWIL (Studi Peran KSPPS BMT Al-Hikmah Bandar Lampung) - Masmuroh, Masmuroh; Mukmin, Hasan; Yanti, Fitri (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2022)
The purpose of this research is to discover how the Shari'a Savings and Loans Cooperative (KSPPS) BMT Pondok Pesantren Al-Hikmah Bandar Lampung implements the economic empowerment strategy and its implications for the community. This is a qualitative study that employs data collection techniques such as interviews and documentation. The author used eight customers as research subjects and two administrators from KSPPS BMT Al-Hikmah. In this qualitative study, data was analyzed before entering the field, while in the field, and after it was completed. In practice, however, data analysis is more focused during the data collection process in the field. The findings of this study indicate that the community economic empowerment strategy implemented was a success, as evidenced by the implementation of three excellent programs, namely empowerment, capacity, and empowerment. The findings indicate that KSPPS BMT Al- Hikmah Bandar Lampung is capable of increasing income and economic welfare, as well as the resilience of the members' families.